MAKNA SIMBOLIK ADAT PULANG BAINDUOK DALAM PERKAWINAN BEDA DAERAH DI DESA PONGKAI ISTIQOMAH KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Syam, Siti Rohayani; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Bainduok's traditional return is to find adoptive parents, tribes and ninik mamak for migrants who want to marry one of the residents in Istiqomah Pongkai Village. But there are still many newcomers who do not understand what the purpose of this custom is, even though the custom of returning to Bainduok is done so that the newcomer is made easy with all matters and makes the official outsider become the Pongkai Istiqomah Village community. The purpose of this study is 1) to know the physical aspects of adat bainduok return, 2) know the social aspects of adat bainduok return, 3) know the values contained in the bainduok return customs.               The author uses qualitative research methods, using symbolic interaction theory. The research location is in Pongkai Istiqomah Village, XIII Koto Kampar District, Kampar Regency. The time of the field research was August 2019 to May 2020. The research subjects were 9 people, determined using a purposive technique. The object of research on the symbolic meaning of the custom of returning home to bainduok in different regional marriages in Pongkai Istiqomah Village. Data collection techniques through interviews, observation and documentation. Data analysis techniques used data reduction, data presentation, and drawing conclusions. Data validity test used participation extension and triangulation.               The results of this research show that the people of Pongkai Istiqomah Village are still practicing this custom because this custom has been passed down for generations. This custom has physical aspects, namely: throbbing, slapping, pencak silat, calempong, goat's head and also mamak ninik clothes. In addition to the physical aspects of adat, it also has a social aspect, namely mutual cooperation and mutual assistance between communities. In this custom there are also some values contained therein, including religious values, social values, and cultural values. Keywords: Bainduok Customary Procession, Istiqomah Pongkai Village